1600 Cryptorchidism and the Value of Ultrasound Scan. (October 2012) - Shoukry, M; Pojak, K; Haddad, M; Choudhry, M
Abstract : Aim: To evaluate the usefulness and accuracy of Ultrasound Scan (USS) in investigating cryptorchidism. Methods: Review of all children with cryporchidism who had undergone USS examination for their testes from February 2010 to October 2010. Preoperative USS findings for presence or absence and position of testes were noted and compared to the operative findings. Sensitivity and specificity of USS examination were calculated. Results: 50 testes in 42 boys were examined by USS preoperatively during the study period. Median age was 6 years. All had single B-mode USS examination using Grey scale and Doppler images. 37 out of 50 testes were palpable on examination under anaesthesia and underwent single stage orchidopexy. All impalpable testes had diagnostic laparoscopy. 2 out of 13 were found atrophic hence excised and rest had staged orchidopexy. USS and operative findings are summarised in the table attached. The sensitivity and specificity of USS in determining the presence of testes were 88% and 4% respectively. Positive predictive value was 52% and negative predictive value was 25%. The sensitivity and specificity of USS in localisation of testicular position were 77% and 4% respectively. Positive predictive value was 32% and negative predictive value was 16%. Position USS findings Operative findings Not visible 6 2 (nubbins) Intra abdominal 2 11 Extra abdominal (intra-canalicular/superfacial inguinal pouch) 42 37 Conclusion: USS Has Low Sensitivity and Specificity in Determining the Presence of Testes and Localisation of Its Position. In the Presence of Examination Under Anaesthesia and Laparoscopic Technique, USS is Not Recommended in Cyptorchidism.